2012
DOI: 10.5301/hip.2012.9747
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation of Primary Total Hip Arthroplasty and the Risk of Redislocation

Abstract: 6554 primary total hip arthroplasties were reviewed. Risk factors for dislocation were analysed to assess which were important in terms of predicting recurrent instability. The patients risk of having a second dislocation was independently associated with the surgical approach adopted (p = 0.03) and the time to first dislocation from the primary hip replacement (p = 0.002). Early dislocators whose surgery was performed through an anterolateral approach had less recurrence than late dislocators through a poster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 15 publications
0
18
0
6
Order By: Relevance
“…Volume 473, Number 11, November 2015 Primary THA Surgical Approach 3405 larger diameter femoral heads, and improved posterior capsular repair after a posterior approach [8,19,20,22,27,47]. Most published studies have indicated that use of larger femoral heads has resulted in overall reduction in rate of dislocation [14,19,20,22,47].…”
Section: Discussionmentioning
confidence: 99%
“…Volume 473, Number 11, November 2015 Primary THA Surgical Approach 3405 larger diameter femoral heads, and improved posterior capsular repair after a posterior approach [8,19,20,22,27,47]. Most published studies have indicated that use of larger femoral heads has resulted in overall reduction in rate of dislocation [14,19,20,22,47].…”
Section: Discussionmentioning
confidence: 99%
“…Von Knoch et al showed that 55 % of the patients with a dislocation after five years had recurrence [12]. Brennan et al also showed that the late dislocation significantly recurred compared to the early dislocation [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite improvements in prostheses, postoperative complications still occur. Among them, dislocation is a severe complication that sometimes leads to revision surgery [ 1 , 2 ], and a meta-analysis has reported hip dislocation to be one of the common causes of THA failure [ 3 ]. Recently, postoperative changes in pelvic tilt have been reported, which cause angular changes of the acetabular components and dislocation [ 4 11 ].…”
Section: Introductionmentioning
confidence: 99%